Knowledge Improvement on Burn Injury Prevention and First Management after One-Day Health Promotion Event - Lisa Hasibuan; Hardisiswo Soedjana; Dany Hilmanto; Vita Murniati Tarawan; Benny Muliawan; Putra Haqiqie Adnantama Lubis (Majalah Kedokteran Bandung, 2019)
Burns causes a significant number of mortality and morbidity globally with a higher number found in developing countries, such as Indonesia. A study conducted in Indonesia discovered that the majority of burns were caused by flame LPG-related (liquefied petroleum gas) burns (33%), which is understandable because LPG is the main cooking fuel used in Indonesian homes. Since the first management of burn will influence the outcome of burn injuries, health promotion efforts to improve knowledge, attitude, and practice to prevent burns and to provide first aid for burn are considered important to reduce burn-related morbidity and mortality. This was a descriptive study conducted in Babakan Sari Sub-district, Antapani, Bandung, Indonesia which involved a one-day community health promotion event as the intervention. The aim of this study was to compare the level of knowledge regarding burn prevention and first management before and after a one-day community health promotion event. As many as 61 respondents were recruited through purposive sampling and these respondents were asked to fill out a pre-event questionnaire consisting of questions regarding demographic data and knowledge on burn prevention and management. Demographic data collected showed that 31% of participants had experienced burns; 100% of participants used 3kg LPG gas tank in their home; 98% of participants had never been taught on how to handle an emergency situation or how to arrange an evacuation route; and 100% of participants felt that their neighborhood did not provide facilities for burn management. A post-event questionnaire was distributed after the one-day health promotion event, which was conducted in October 2018, and the results were compared with the pre-event questionnaire results. A significant improvement of knowledge was seen, as evident from the increase of a median score from 2.0 before the event to 9.0 after the event (p<0.001). In conclusion, despite the fact that all participants of this study used 3kg LPG gas tank, they do not have proper knowledge regarding prevention or management of burns and that a one-day health promotion event can increase this knowledge significantly. Thus, an effective community health promotion program should be implemented at the community level in Indonesia, especially for areas where the majority of residents use 3 kg LPG gas tank, in order to reduce the incidence of burns due to 3 kg LPG tank explosion.Peningkatan Pengetahuan Melalui Penyuluhan Mengenai Pencegahan dan Penanganan Dini pada Luka BakarLuka bakar merupakan sebuah masalah yang menyebabkan morbiditas dan mortalitas tinggi di negara berkembang, termasuk Indonesia. Mayoritas luka bakar (33%) diakibatkan oleh api dari ledakan tabung gas LPG (liquefied petroleum gas) 3 kg dan mayoritas rumah tangga menggunakannya. Pelaksanaan penyuluhan mengenai pencegahan dan penanganan awal diharapkan dapat menurunkan angka morbiditas dan mortalitas akibat luka bakar. Penelitian deskriptif ini bertujuan membandingkan tingkat pengetahuan tentang pencegahan luka bakar dan manajemen pertama sebelum dan setelah acara promosi kesehatan Penelitian ini dilakukan di Kelurahan/Desa Babakan Sari, Antapani, Bandung pada bulan Oktober 2018 untuk mengedukasi dan meningkatkan pengetahuan responden. Dari total 61 responden (45 wanita dan 16 pria) dengan mayoritas responden berusia di atas 60 tahun (45.9%), didapatkan 32.8% responden pernah mengalami luka bakar, 100% responden menggunakan gas LPG 3 kg, 98% peserta tidak pernah mendapatkan penyuluhan mengenai penanganan luka bakar, dan 100% peserta merasa tidak ada fasilitas penanganan kebakaran di wilayah mereka. Pengetahuan responden dinilai sebelum dan sesudah dilakukan penyuluhan dan didapatkan peningkatan secara signifikan dan bermakna (p<0.001). Simpulan, meskipun semua responden yang menggunakan tangki gas LPG 3 kg tidak memiliki pengetahuan yang memadai pencegahan atau pengelolaan luka bakar, penyuluhan ini efektif dapat menurunkan angka kejadian luka bakar.